The Influence of TikTok Social Media on Adolescent Social Behavior in the Digital Era: A Case Study in Kendari City - Sari, Dyah Fitria Kartika (Yayasan Sinergi Kawula Muda, 2025)
This study examines the role of TikTok in shaping the social behavior and self perception of adolescents in Kendari City, Indonesia. Situated within an interpretivist paradigm, a qualitative descriptive case study was conducted involving 120 adolescents aged 15–18 years. Data collection employed participatory observation, baseline questionnaires, and semi structured interviews, analyzed through thematic coding and matrix displays. The findings reveal that TikTok usage fosters both positive and negative psychosocial outcomes. While 42% of respondents reported increased self confidence through creative engagement, 32% experienced social pressure to conform to trending challenges, and 12% reported negative social comparisons. Algorithmic recommendation systems were found to significantly influence content exposure and behavioral normalization, aligning with the emerging